Recurrent Nocturnal Chest Pain in an Elderly Patient: A Case Report of Variant Angina - Awan, Shakeel Ahmad; Cooper, Nicola; Muaz, Umer; Khan, Saleem (Indus Journal of Bioscience Research, 2025)
Background: Variant angina, also referred to as Prinzmetal angina, is typified by intermittent episodes of coronary artery spasm that produce discomfort in the chest at rest and raise the ST-segment on the ECG. Diagnosing this condition may be challenging because it develops suddenly and has transient clinical signs. Case Presentation: A 75-year-old man arrived complaining of five weeks of night-time, largely restful, episodes of severe chest pain. A normal physical examination and a slight rise in troponin were the results of the initial testing. Following coronary angiography, a drug eluting balloon was inserted into the LAD to treat mid-LAD stenosis. Despite receiving initial treatment, the patient continued to experience chest pain; an ECG showed a transient elevation of the ST segment; angiography later revealed severe RCA stenosis and LAD restenosis. Drug-eluting stents were implanted in both arteries, and the use of GTN significantly lessened discomfort. Echocardiography revealed normal cardiac function at the time of discharge. Conclusion: The need of taking Variant Angina into account in patients with transient ST segment alterations and nocturnal chest discomfort is emphasized by this example. Patient quality of life can be enhanced and good results can result from appropriate diagnosis and treatment with nitrates and calcium channel blockers.